MEMS-Based Electrochemical Seismometer with a Sensing Unit Integrating Four Electrodes - Wenjie Qi (Micromachines, 2021)
This paper presents a new process to fabricate a sensing unit of electrochemical seismometers using only one silicon–glass–silicon bonded wafer. By integrating four electrodes on one silicon–glass–silicon bonded wafer, the consistency of the developed sensing unit was greatly improved, benefiting from the high alignment accuracy. Parameter designs and simulations were carried out based on this sensing unit, which indicated that the sensitivities of the developed electrochemical seismometer decreased with the decrease in the number of flow holes in the sensing unit, and the initial stabilization time decreased gradually with the decrease in the thickness of the glass layer. Based on experimental results of four devices, the peak sensitivity was quantified as 5345.45 ± 43.78 V/(m/s) at 2 Hz, which proved high consistency of the fabricated electrochemical seismometer. In terms of the responses to random ground motions, high consistencies between the developed electrochemical seismometer and the commercial counterpart of CME6011 (R-sensors, Moscow, Russia) were found, where the developed electrochemical seismometer produced comparable noise levels to those of CME6011. These results validated the performance of the device and it may function as an effective tool for a variety of applications.